WAQF INSTITUTIONS IN KUWAIT: HISTORICAL PERSPECTIVE - Al-Daihani, Meshari; Che Abdullah, Ahmad Sufian; Madun, Azian (Jurnal Syariah, 2023)
Waqf is an Islamic financial institution that can be operated to fulfil the various needs of the Muslim community. This qualitative-based research aims to review the beginnings of waqf in Kuwait up until the current day. It also aims to explain the Kuwait Awqaf Public Foundation experience as well as highlight the works of waqf institutions and their waqf share schemes. It can be concluded that Kuwait has a very rich waqf history and a considerable present experience, with variations between government and private practice.